2018
DOI: 10.1016/j.jaci.2017.12.690
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Long Term Opioid Use in Patients with Asthma and Allergic Rhinitis

Abstract: Proper understandings of local factors related with poor asthma control are fundamental to care givers in order to develop health strategies. Recent literature says that anxiety and depression are common among patients with poor control asthma. It is imperative to acknowledge that cultural differences from country to country may impact in this association. METHODS: It is an Observational, descriptive, anonymous crosssectional survey study, conducted in the outpatient Respirology department of private hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although the role of comorbid allergic diseases in OUD is not clear, the prevalence of asthma in patients with OUD has previously been found to be higher than the national prevalence of asthma. 47,48 The associations found in our study clearly highlight the need for future, prospective studies to more definitively address the role of atopy and reported NSAID allergies in prescribing patterns and development of opioid use disorder.…”
Section: Discussionmentioning
confidence: 64%
“…Although the role of comorbid allergic diseases in OUD is not clear, the prevalence of asthma in patients with OUD has previously been found to be higher than the national prevalence of asthma. 47,48 The associations found in our study clearly highlight the need for future, prospective studies to more definitively address the role of atopy and reported NSAID allergies in prescribing patterns and development of opioid use disorder.…”
Section: Discussionmentioning
confidence: 64%
“…Nonmedical drug use directly affects the pulmonary system (e.g., pulmonary edema) ( Radke et al., 2014 ; Tseng et al., 2013 ). Evidence suggests drugs, including opioids, increase asthma prevalence above the national average ( Naik et al., 2018 ; Lee et al., 2019 ). Drugs also affect the cardiovascular system, with studies showing a link between long-term use of opioids, cocaine, and certain amphetamines with cardiac structural changes such as myocardial fibrosis ( Aquaro et al., 2011 ; Kevil et al., 2019 ; Seltenhammer et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%